LRP1 at the crossroads of Aβ clearance and therapeutic targeting in Alzheimer’s disease - Deng, Yuepeng; Yin, Haolin; Lu, Zihao; Lan, Huan; Liu, Wenxiong; Zuo, Chao; Pan, Nanfang; Tian, Xiaohe; Gong, Qiyong (Frontiers in Aging Neuroscience, 2026)
Alzheimer’s disease (AD), characterized by progressive cognitive decline, memory impairment and behavioral disturbances, is the most common form of dementia, and no disease-modifying treatments are available to halt or slow its progression. Amyloid-beta (Aβ) is suggested to play a pivotal role in the pathogenesis of AD, and enhancing the clearance of Aβ from the brain has emerged as a major research direction. As the primary receptor for Aβ clearance at the blood-brain barrier (BBB), low-density lipoprotein receptor-related protein 1 (LRP1) plays a crucial role in regulating Aβ transport and metabolism. Understanding the mechanisms through which LRP1 functions, as well as the factors that influence its activity is essential for enhancing Aβ clearance from the brain and developing targeted therapeutic strategies for Alzheimer’s disease. In this review, we introduce the transport of Aβ across the BBB, followed by a discussion of the basic structure and function of LRP1 and its role in AD progression. Then, we summarize factors affecting LRP1 function and current advances in LRP1-targeted therapies. Finally, we explore the potential of LRP1 as a therapeutic target for AD. So, LRP1 may be a central modulator of Aβ dynamics and a clinically actionable target for treatment of Alzheimer’s disease.